Advances in mergers and acquisitions. Vol. 20 - Cooper, Cary L.; Finkelstein, Sydney (Advances in mergers and acquisitions ;, 2021)
Advances in Mergers and Acquisitions stands out from the competition due to its focus on three key characteristics: studies from scholars in different countries, with different research questions, relying on different theoretical perspective. Such a broad and inclusive approach to mergers and acquisitions is not easily replicated in academic journals, with much narrower mandates and metrics. The chapters published in this volume provide cutting edge ideas by leading scholars and help to inform mergers and acquisitions research around the world. Volume 20 of this annual series explores a range of issues relevant to a post-Covid world and the ensuing recession. These include creative ways to bridge the gaps between buyers and sellers, mitigating cross border acquisition uncertainties, M & A investment decision-making, as well as how customers experience an acquisition and whether merging firms perceive their customers as assets to trade or as stakeholders to engage. This book is of interest to scholars in strategic management, organization theory, and organizational behaviour who are studying questions around mergers and acquisitions. Doctoral students in particular will benefit from access to the diversity of research that can trigger new research questions and expanded research agendas.